Effect of structural parameters on the impact properties of multilayer composites from Tururi palm (Manicaria saccifera Gaertn.) fibrous material. Issue 2 (1st February 2020) - Midani, Mohamad; Seyam, Abdel-Fattah M.; Monteiro, Amanda Sousa; Baruque-Ramos, Julia
ABSTRACT: Tururi ( Manicaria saccifera Gaertn.) is a natural fibrous mesh which protects the fruits of the Amazon Ubuçu palm tree. This research targets developing natural fiber composites from Tururi fibers and characterizing their impact properties. A set of composites from Tururi fiber with different construction parameters (number of layers, fiber orientation, and fiber volume fraction) were manufactured. The results indicated that increasing the number of layers significantly increased the impact resistance up to a limit after which the resin penetration is impaired; moreover, stretching the preform significantly reduced the fiber volume fraction, and hence the impact properties. Finally, the fiber orientation had a negligible effect on the impact energy; yet, it had a significant effect on the failure mechanism.